2015
DOI: 10.1111/iwj.12434
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of angiogenesis, epithelialisation and microcirculation after application of polyhexanide, chitosan and sodium chloride in rodents

Abstract: The purpose of this study was to investigate the effect of polyhexanide and a new developed chitin-based wound dressing on skin microcirculation, epithelialisation and angiogenesis. A full-thickness dermal layer extending to the underlying cartilage was excised on the dorsal side of hairless mice (n = 27; 2·3 ± 0·3 mm ). A polyhexanide ointment, a chitosan solution and a sodium chloride group as control were analysed using intravital fluorescence microscopy. Angiogenesis, epithelialisation and microcirculatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In a recent systematic review, it was concluded that PHMB may promote the healing of chronic wounds, reduce the bacterial load, eradicate MRSA, and lessen wound‐related pain 151 . A preclinical study using a mouse wound model demonstrated that PHMB had more beneficial effects on the microcirculation, angiogenesis, and epithelialisation compared with chitosan 152 . In a further study, PHMB had a more positive effect upon the blood flow of intact human skin in vivo than octenidine, suggesting value in the treatment of critically perfused wounds, such as burns 142 .…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…In a recent systematic review, it was concluded that PHMB may promote the healing of chronic wounds, reduce the bacterial load, eradicate MRSA, and lessen wound‐related pain 151 . A preclinical study using a mouse wound model demonstrated that PHMB had more beneficial effects on the microcirculation, angiogenesis, and epithelialisation compared with chitosan 152 . In a further study, PHMB had a more positive effect upon the blood flow of intact human skin in vivo than octenidine, suggesting value in the treatment of critically perfused wounds, such as burns 142 .…”
Section: Resultsmentioning
confidence: 93%
“…151 A preclinical study using a mouse wound model demonstrated that PHMB had more beneficial effects on the microcirculation, angiogenesis, and epithelialisation compared with chitosan. 152 In a further study, PHMB had a more positive effect upon the blood flow of intact human skin in vivo than octenidine, suggesting value in the treatment of critically perfused wounds, such as burns. 142 Comparison of a PHMB-containing dressing with a silver-based dressing in patients with critically colonised and locally infected wounds demonstrated that the PHMBcontaining dressing was significantly faster and more effective at removing the critical bacterial load over a 28-day period.…”
Section: Polyhexanidementioning
confidence: 80%